Superficial acral fibromyxoma on the palm: a case report - Chunli Yang; Bin Lu; Zheng Lin (Journal of Medical Case Reports)
Abstract Background Superficial acral fibromyxoma is a noncancerous, benign tumor of soft tissue with an unidentified origin. Occurrences of abnormalities on the palm are less frequently documented. Case report presentation A 47-year-old East Asian woman presented with a palm tumor on her left knuckle that had been present for 4 months. Four months prior to treatment, a reddish nodule appeared at the site due to continuous friction, but the patient did not pay attention to it. Upon physical examination, a pale-reddish nodule measuring approximately 0.8 × 0.8 cm was observed on the flexion side of the fourth metacarpophalangeal joint of the left hand. The nodule was nearly round, exhibited distinct margins, featured slight surface keratosis, and displayed a collar-like alteration at its periphery. The stroma showed significant fibrous proliferation and a myxoid matrix. The cellular composition consisted primarily of spindle-shaped fibroblasts, which were locally arranged in bundles within the stroma. Sparse slender blood vessels were distributed along with observed red blood cell extravasation. Immunohistochemistry of the tumor showed CD34 (+), CD99 (−), desmin (−), epithelial membrane antigen (−). Extensive resection of the mass was performed. Conclusion A rounded mass on the palm of the hand may be superficial acral fibromyxoma. The optimal approach for treating superficial acral fibromyxoma involves complete surgical removal of the mass followed by postoperative monitoring.